Christianity and the Gendering of Personal Names among the Bette in Southeastern Nigeria - Aboh, R.; Mensah, E.; Inyabri, I.; Ushuple, L. (Journal of Religion in Africa, 2022)
Contributing to extant debates on the juncture of naming and gendering, this study interrogates naming practices among Bette-Christians of northern Cross River, Southeastern Nigeria, and how they enhance understanding of the relationship between naming and the enunciation of religious identity, as well as how gender is enacted. With analytical insights from socio-onomastic theory, which explores the relationship between names, culture, and society, we interrogate naming practices as essential cultural currency for identification, categorization, and connectedness. Data were obtained from 40 participants through semistructured interviews and participantobservations. We focus on the intersection of naming and spiritual sentiments to argue that the contemporary reality of naming among Bette-Christians illuminates a practice that negates traditional Bette cosmology and cosmogony. We illustrate how the emergence of Christianity has altered the naming patterns and practices of the people. and how these names embody multidimensional connotations that range from religious identity to stereotyped gender ideologie
Research Article
Keywords: personal names; Bette-Christians; religious identity